Adolescent Nutrition—Developing a Research Agenda for the Second Window of Opportunity in Indonesia. Issue 1 (June 2021) - Sparrow, Robert; Agustina, Rina; Bras, Hilde; Sheila, Grace; Rieger, Matthias; Yumna, Athia; Feskens, Edith; Melse-Boonstra, Alida
Background: Recently, adolescence has been identified as a second window of opportunity for the correction of nutritional inadequacies. However, there is a lack of knowledge on evidence-based integrated nutrition strategies for adolescents in Indonesia. Objective: To provide a research agenda and the prioritization of research actions to tackle outstanding knowledge gaps on adolescent nutrition in Indonesia. Methods: A preliminary set of research topics was listed based on a desk study of the academic literature and policy documents. Second, a stakeholder meeting was held to further identify and discuss research topics related to adolescent nutrition in Indonesia. Third, an online survey was conducted in which respondents were asked to indicate priority research themes for the next 3 to 5 years and to rank a total of 23 research questions. Results: Most (52%) of the respondents who returned the survey (n = 27) prioritize research on implementation and program evaluation, while 30% prefer descriptive and explanatory research, and 19% place priority with intervention and discovery research. However, when we followed up with specific topics for each of these broad research areas, a more nuanced picture emerged, with intervention and discovery research taking a more prominent standing. Conclusions: In order to support the design, implementation, and effectiveness of integrated nutrition programs for Indonesian adolescents, in-depth studies should question the best intervention strategies, modes of delivery, and long-term outcomes, while nationwide and disaggregated data should investigate associations and trends over time and identify vulnerable groups.